Nanoparticles and Radioisotopes: A Long Story in a Nutshell - Giulia Poletto; Laura Evangelista; Francesca Venturini; Fabiana Gramegna; Flavio Seno; Stefano Moro; Roberto Vettor; Nicola Realdon; Diego Cecchin (MDPI AG, 2022)
The purpose of this narrative review was to assess the use of nanoparticles (NPs) to deliver radionuclides to targets, focusing on systems that have been tested in pre-clinical and, when available, clinical settings. A literature search was conducted in PubMed and Web of Science databases using the following terms: "radionuclides" AND "liposomes" or "PLGA nanoparticles" or "gold nanoparticles" or "iron oxide nanoparticles" or "silica nanoparticles" or "micelles" or "dendrimers". No filters were applied, apart from a minimum limit of 10 patients enrolled for clinical studies. Data from some significant studies from pre-clinical and clinical settings were retrieved, and we briefly describe the information available. All the selected seven classes of nanoparticles were highly tested in clinical trials, but they all present many drawbacks. Liposomes are the only ones that have been tested for clinical applications, though they have never been commercialized. In conclusion, the application of NPs for imaging has been the object of much interest over the years, albeit mainly in pre-clinical settings. Thus, we think that, based on the current state, radiolabeled NPs must be investigated longer before finding their place in nuclear medicine.